A vindication of William Penn, proprietary of Pennsilvania : from the aspersions spread abroad on purpose to defame him - Ford, Philip, -1702 (Printed for Benjamin Clark, 1683)
1683 Publication by Philip Ford which presented a vindication of William Penn against defaming aspersions. Included were allegations that Penn was a "Papist," that he used Jesuit priests to write his book and other "slanders."